1992
DOI: 10.1002/ajpa.1330880106
|View full text |Cite
|
Sign up to set email alerts
|

Relations between sex hormone level and characters of hair and skin in healthy young men

Abstract: Total testosterone and dihydrotestosterone in blood serum as well as free testosterone in saliva were determined by radioimmunoassay in 110 healthy young men. The results were compared with the development of terminal hair on the trunk and limbs, with the disposition to balding and with the disposition to acne. No significant correlations were found between terminal hair development and absolute androgen levels; however, some significant values were observed in the case of the metabolic rate of dihydrotestoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 48 publications
(46 reference statements)
1
15
0
1
Order By: Relevance
“…In another group, healthy young men showed a disposition to balding in those subjects with an increased ratio of 5a-DHT/ testosterone. Absolute serum testosterone levels were not associated with balding patterns (177). Differences in beard growth, body hair and balding seen between races are probably determined by various degrees of 5a-reductase activity; the ratio 5a-DHT:testosterone was higher in Caucasians than in Asians living in the US and Canada (112).…”
Section: Hair Patternmentioning
confidence: 99%
“…In another group, healthy young men showed a disposition to balding in those subjects with an increased ratio of 5a-DHT/ testosterone. Absolute serum testosterone levels were not associated with balding patterns (177). Differences in beard growth, body hair and balding seen between races are probably determined by various degrees of 5a-reductase activity; the ratio 5a-DHT:testosterone was higher in Caucasians than in Asians living in the US and Canada (112).…”
Section: Hair Patternmentioning
confidence: 99%
“…Although facial and body hair are androgen dependent (Randall, 2008), variation in total testosterone, the highest serum levels of androgens, does not explain within-or between-population differences in facial or body hair density and patterning (Ewing & Rouse, 1978;Knussmann, Christiansen, & Kannmacher, 1992;Lookingbill et al, 1991;Winkler & Christiansen, 1993). Instead, these terminal hairs develop due to the combined effects of testosterone and its 5a reductase metabolite dihydrotestosterone (DHT) (Randall, 2008).…”
Section: Introductionmentioning
confidence: 96%
“…Published studies in men have found that MPH is positively correlated with DHT, DHT/T and T/E 2 (Knussmann et al, 1992;Winkler and Christiansen, 1993). Given this link, it is of interest to consider other potential health and behavioral correlates of DHT and T that could be examined in future MPH research.…”
Section: Potential Value Of Mph In Health or Behavioral Researchmentioning
confidence: 96%
“…However, these studies examined men of German descent and men living as hunter and gatherers in South Africa. The two studies found significant positive relationships between MPH and both DHT (Winkler and Christiansen, 1993) and DHT/T ser (DHT/serum T; Knussmann et al, 1992;Winkler and Christiansen, 1993). Serum T consists of both bound and unbound T, and DHT/T ser has been used as an estimate of 5␣-reductase activity.…”
Section: Middle Phalangeal Hair and Hormonesmentioning
confidence: 96%
See 1 more Smart Citation